Safety Stock Placement Pada Perusahaan Farmasi Menggunakan Pendekatan Guaranteed-Service Dalam Jaringan Fasilitas Produksi - Pinasthika Dharaka, Kumara; Rizkiyah, Ega; Angella Pranoto, Nathania (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2022)
This study aims to understand the supply chain strategy of pharmaceutical companies, logistics drivers (facilities, inventory, and transportation), and cross-functional drivers (information, sources, and prices), as well as the problem of placing safety stock for assembly, using an integer linear approximation program using CPLEX to get the results and perform a sensitivity analysis. In this way, the effect of various parameters on total safety stock and service time can be estimated. Pharmaceutical companies can find strategic ways to align their goals with this method. The company already has an optimal supply chain focused on product quality, short response times, and product availability. In addition, it can minimize the total cost of safety inventory by using a piecewise linearization approach with a total assembly cost of Rp. 6,161,120,000, where safety stock is stored in stages 2-4, 7-14, 16, and 22, where 22 has the highest stage costs. Then a sensitivity analysis is carried out by allowing the parameters to vary, the more segments' total cost becomes stable. Furthermore, the relationship between the factors of safety, storage costs, and standard deviation is linear.